Experimental Study of Simultanoeus Transmission of a Light Wave and an Ultrasonic Wave in an Optical Fiber with the Use of a Mach-Zehnder Interferometer - MUC, Sylwia; GUDRA, Tadeusz; BEREŚ-PAWLIK, Elżbieta (Archives of Acoustics, 2009)
The possibility of acoustic wave propagation in optical waveguides creates new prospects for the simultaneous use of a light wave and an ultrasonic wave in, for instance, medicine for cutting biological tissues with a surgical ultrasonic laser knife. A Mach-Zehnder optical waveguide interferometer was used in the experimental studies of simultaneous transmission of those two wave types. If ultrasonic vibrations are delivered to one of the interferometer arms, a light modulation effect is produced. This paper presents measurement results for different methods of delivering ultrasonic waves to the optical fiber, i.e. using radial vibrations of a piezoelectric disk or longitudinal vibrations generated by a sandwich ultrasonic transducer with a velocity transformer.